2019
DOI: 10.1111/ijcs.12518
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing environmentally sustainable apparel: The attitudes and intentions of female Kuwaiti consumers

Abstract: The purpose of this study is to examine relationships among knowledge, environmental concern, attitudes about environmentally sustainable apparel (ESA) and ESA purchasing behaviours of Kuwaiti women. This was accomplished by surveying 236 participants using four preexisting scales, measuring knowledge about the impact of manufacturing apparel and textile products on the environment, levels of concern about environmental degradation, feelings about clothing that is environmentally sustainable and ESA purchase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…According to classical theories in consumer behavior domain, specifically the theory of planned behavior, behavior of an individual can-to some extent-be reasonably deduced by his or her behavioral intention, and behavioral intention-the subjective possibility of a specific behavior-can be used as a measurement for a specific behavior [23,25]. Much research has concluded that green consumption intention can effectively profile green consumption behavior [8,23,26,27]. Moreover, the academic community has extensively explored the influence mechanism of green consumption intention [7,14,[28][29][30], which can be classified into three mainstreams.…”
Section: Green Consumptionmentioning
confidence: 99%
“…According to classical theories in consumer behavior domain, specifically the theory of planned behavior, behavior of an individual can-to some extent-be reasonably deduced by his or her behavioral intention, and behavioral intention-the subjective possibility of a specific behavior-can be used as a measurement for a specific behavior [23,25]. Much research has concluded that green consumption intention can effectively profile green consumption behavior [8,23,26,27]. Moreover, the academic community has extensively explored the influence mechanism of green consumption intention [7,14,[28][29][30], which can be classified into three mainstreams.…”
Section: Green Consumptionmentioning
confidence: 99%
“…Psychological factors mainly include environmental attitude, social norms, self‐affirmation, environmental consciousness, motivation, values, the internal locus of control and personal responsibly. (Albloushy & Connell, 2019; Gifford & Nilsson, 2014; Graham‐Rowe, Jessop, & Sparks, 2019; He, Duan, Wang, & Fu, 2019; Kautish, Paul, & Sharma, 2019; Kim & Seock, 2019; Paul, Modi, & Patel, 2016). Situational factors include interpersonal relationships, laws, the convenience of recycling facilities, green product quality and green product packaging (Herbes, Beuthner, & Ramme, 2020; Rana & Paul, 2020).…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
“…Ajzen & Fishbein (1980) identified attitudes as predictors of behavior and behavioral intentions. Attitudes towards a product can exclusively determine the purchasing intention toward that product (Albloushy & Connell, 2019). Attitudes have served as predictors of energy-conservation behavior, product usage and recycling, and ecologically-conscious purchasing behavior (Schneider & Vogt, 2012).…”
Section: Hypothesis Developmentmentioning
confidence: 99%